Talking Stick and Question Box as a Cooperative Learning Strategy: Improving Student Participation in Science and Social Studies Learning - Ni Komang Ita Finanti; Zulnuraini Zulnuraini; Asriani Asriani; Arif Firmansyah; Sri Wahyuni (Journal of Innovation and Research in Primary Education, 2026)
Low student learning engagement in interdisciplinary Science and Social Studies Learning (Ilmu Pengetahuan Alam dan Sosial/IPAS) instruction remains a persistent challenge in Indonesian elementary education, particularly under the Merdeka Curriculum framework that demands active, student-centered participation. This study examined the effect of the Talking Stick learning model assisted by Question Box media on student learning engagement among 16 fifth-grade students at SDN Tindaki, Parigi Moutong Regency. A quantitative quasi-experimental design with a One Group Pretest-Posttest approach was employed. Data were collected using a learning engagement questionnaire and an observation sheet, measuring four behavioral indicators: enthusiasm for participation, willingness to ask questions, courage to answer, and confidence in presenting understanding. Instrument validity was confirmed through Pearson Product Moment correlation, and reliability through Cronbach's Alpha. Data were analyzed using descriptive statistics and a Paired Sample t-test via SPSS version 30. The results showed a significant increase in mean engagement scores from 58.44 (pretest) to 62.00 (posttest), with a Paired Sample t-test yielding p = 0.003 (p < 0.05). All four behavioral indicators improved, with the greatest gains recorded for enthusiasm for participation (+7.8%) and courage to present understanding (+7.5%). These findings confirm that the Talking Stick–Question Box combination is an effective, accessible strategy for fostering behavioral engagement in elementary IPAS learning and warrants broader adoption within the Merdeka Curriculum context.